2013
DOI: 10.3945/ajcn.112.048074
|View full text |Cite
|
Sign up to set email alerts
|

Improved 4-compartment body-composition model for a clinically accessible measure of total body protein

Abstract: A simple method to measure total body protein by using a DXA system and BIA unit was developed and compared with NAA as proof of principle. With additional validation, this method could provide a clinically useful way to monitor muscle-wasting conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 29 publications
3
47
1
1
Order By: Relevance
“…Older quantitative investigative techniques used to assess muscle mass included urinary creatinine excretion or underwater weighing which have suboptimal accuracy and provide limited information. Other more experimental techniques include neutron activation analysis and air displacement plethysmography which are highly accurate but not practical in the clinical setting . There are, however, techniques that can be performed within a normal hospital setting using easily accessible methods.…”
Section: Diagnosis Of Sarcopeniamentioning
confidence: 99%
“…Older quantitative investigative techniques used to assess muscle mass included urinary creatinine excretion or underwater weighing which have suboptimal accuracy and provide limited information. Other more experimental techniques include neutron activation analysis and air displacement plethysmography which are highly accurate but not practical in the clinical setting . There are, however, techniques that can be performed within a normal hospital setting using easily accessible methods.…”
Section: Diagnosis Of Sarcopeniamentioning
confidence: 99%
“…4C body composition was calculated with the use of the Lohman method (8) and the simplified DXA + BIA approach of Wilson et al (7). Linear regression analysis was performed to determine the agreement between body composition methods.…”
Section: Methodsmentioning
confidence: 99%
“…This device uses the frequencies ranged from 50 to 250 kHz, is affordable, and is not invasive (17,18). The comparison of this method with X-ray showed that it accurately assessed body composition (19)(20)(21). By this method, WHR, BMI, the percentage of body fat (PBF), total fat (TF), and FFM were measured, using the standard positions of outer and inner electrodes on the hand and foot (8 electrodes) (22,23).…”
Section: Methodsmentioning
confidence: 99%